2006
DOI: 10.2170/physiolsci.rp006506
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Histamine Type-1 Receptor to Metabolic and Behavioral Control of Ventilation

Abstract: Histaminergic neurons in the hypothalamus are well documented as being involved in the control of autonomic functions, such as the balance of energy metabolism and circadian rhythm. We tested the hypothesis that an activation of the histamine type-1 (H1) receptor is required for the control of ventilation during the course of a day in free-moving mice. Ventilation, aerobic metabolism, and electroencephalogram were measured by a whole-body-plethysmograph, a magnetic-type mass spectrometry system, and a telemetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…Moreover, electroencephalography in Hdc −/− mice demonstrates increased power density of cortical ␦-waves, but reduced power density of cortical rhythm during wakefulness, as compared to wild-type controls (Parmentier et al, 2002). This may be a consequence of missing H 1 R activation in Hdc −/− mice, since an increased ␦/ wave ratio during the dark phase has also been found in Hrh1 −/− mice, which was interpreted as a state of reduced arousal (Ishiguro et al, 2006).…”
Section: Sleep-wake Cycle and Circadian Rhythmmentioning
confidence: 87%
“…Moreover, electroencephalography in Hdc −/− mice demonstrates increased power density of cortical ␦-waves, but reduced power density of cortical rhythm during wakefulness, as compared to wild-type controls (Parmentier et al, 2002). This may be a consequence of missing H 1 R activation in Hdc −/− mice, since an increased ␦/ wave ratio during the dark phase has also been found in Hrh1 −/− mice, which was interpreted as a state of reduced arousal (Ishiguro et al, 2006).…”
Section: Sleep-wake Cycle and Circadian Rhythmmentioning
confidence: 87%
“…We previously studied the metabolic rate throughout a 24-h measurement period under normoxic conditions. H1RKO mice show higher R values than WT mice, suggesting a predominance of glycolytic metabolism [42]. This metabolic trait was thought to be advantageous for anaerobic metabolism during hypoxia.…”
Section: Genotype Variations In Ventilatory and Metabolic Responses Tmentioning
confidence: 99%
“…Ventilation endogenously oscillates throughout the day, similar to metabolism and other physiological variables [1,2]. In nocturnal animals such as rodents, ventilation and metabolism are higher in the dark period than in the light one.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, we observed biphasic ventilatory responses to normocapnic hypoxia in mice. We added 3% CO 2 to the hypoxic gas to maintain a constant level of arterial PCO 2 (PaCO 2 ) [2,4,7]; this prevents hypocapnia induced by hypoxic hyperventilation [8]. Indeed, our previous blood gas analyses in mice showed PaCO 2 levels of 36-39 mmHg at 10 min after 7% O 2 inhalation adding 3% CO 2 [4, 9], but 19 mmHg at the same time after 7% O 2 inhalation [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation